New potent epitopes from Leptospira borgpetersenii for the stimulation of humoral and cell-mediated immune responses: Experimental and theoretical studies - Yada Tansiri; Tepyuda Sritrakul; Patchreenart Saparpakorn; Timporn Boondamnern; Aunlika Chimprasit; Sineenat Sripattanakul; Supa Hannongbua; Siriwan Prapong (My University, 2021)
The rhKU_Sej_LRR_2271 protein is introduced as one of the leptospiral vaccine candidates since it contains the predicted immunogenic epitopes. The in-silico sequence and structural based analysis have been used in this study to analyze MHC class I and class II-restricted epitopes of the protein. Six epitope prediction programs were employed, which the epitopes with high prediction scores from each program were aligned. The 21 of potentially unrestrained epitopes with prediction scores above the cut-off value from at least two prediction programs were selected. The 3D-molecular modeling, docking, and molecular dynamic simulation were performed to evaluate the affinity binding between peptide-MHC complex and T-cell receptor. One promising epitope, which is 171-LLFLPLIKI, showed the potency in binding to both MHC class I and II alleles. Two newly designed peptides containing epitopes which can bind to over 3 of MHC alleles, LL17:171-LLFLPLIKILYVDRNKL-187 and SL19:209-SLNSGIKALPFNYEKLVNL-227, significantly increased interferon-gamma (IFNg)-producing specific T-cell responses in the rhKU_Sej_LRR_2271 immunized rabbits compared to nonimmunized rabbits. The LL17 peptide can also induce interferon-gamma-producing specific CD4+ T-cell responses in the immunized rabbits. For the evaluation of humoral immune responses, the immunized rabbits have a significantly greater amount of specific IgG in plasma than the nonimmunized rabbits. Ex-vivo study of T-cell responses in animal model using flow cytometry confirmed an accomplishment of the theoretically in-silico analysis for discovering potential T-cell epitopes of the protein. The results show that the rhKU_Sej_LRR_2271 protein containing promiscuous T-cell epitopes, which can induce both humoral and cell-mediated immune responses, is a prospective protein candidate for leptospiral vaccine development.
Keywords: Leptospirosis research and findings